Studi Perbandingan Kadar Ni dan Fe Berdasarkan Sampel Cek Pit dan Sampel Cek Stock Pile Mining Nikel pada PT. Bintangdelapan Mineral Sulawesi Tengah - Sambari, Villa Evadelvia Ginal (Universitas Dr. Soetomo, 2021)
Nickel mining in PT. Bintangdelapan Mineral District located in the village Fatufia Bahodopi Morowali, Central Sulawesi. The purpose of this research study sampling techniques and sample checks pit stock pile, and aimed to compare the levels of Ni, Fe. The authors limit the issues on comparative levels of Ni, Fe, based on sampling and sample checks pit mining production and production sample port stock pile, using the analysis tool Minipal. Field research methods consisting of the preparation stage, the stage of data collection, data processing stage and phase of Thesis. Results in getting the checks on the sampling pit, mining samples, and sample port is an increase in levels, this is because the mining PT. Bintangdelapan Minerals has applied to both selective mining mining methods. In this sample, the researcher applied sampling method and sample check stock pile pit nickel laterite operations in accordance with standard PT. Bintangdelapan Minerals, the data obtained is processed using Microsoft Excel and then presented in the form of reading SPSS (Statistical Product And Service Solution).